Evaluation of correlation of serum vitamin B12 with proteinuria in type 2 Diabetes Mellitus patients - Kalbasi, Saeed; Sadat Zahed, Narges; Samavat, Shiva; Gachkar, Latif; Davoudi, Zahra; Haghverdilou, Fariba (Student Research in Translational Medicine, 2021)
Background and aims: Diabetic nephropathy is one of the leading causes of end stage renal disease (ESRD) in the world. This study was conducted to investigate the correlation of B12 deficiency with presence of proteinuria in patients with Diabetes Mellitus. Materials and Methods: This study was performed on patients with type 2 Diabetes Mellitus. The inclusion criteria were: HbA1C ≤8%, absence of hypertension or controlled blood pressure (BP<140/90) in hypertensive patients, no smoking, absence of any recent stressful illness such as MI, CVA and causes of proteinuria other than diabetic nephropathy. The serum level of B12 and the amount of urine protein–to-creatinine ratio (UPCR) were measured, and correlation between b12 deficiency and presence of proteinuria was assessed using Spearman correlation test. Results: In this study 78 patients (44.87% women and 55.13% men) were examined. There was an inverse and weak correlation between the serum B12 deficiency and presence of proteinuria (r = -0 / 104), which was not statistically significant (p = 0.254). Due to the statistically significant difference between two groups with and without proteinuria in antiproteinuric drugs, as well as Metformin use and chronic kidney disease (CKD) stage, a subgroup analysis was performed in each of these subgroups. There was no correlation between the B12 deficiency and presence of proteinuria. Conclusion: The findings revealed no statistically significant correlation between the serum B12 deficiency and presence of proteinuria.